New experimental insights into magneto-mechanical rate dependences of magnetorheological elastomers - Moreno Mateos, Miguel Angel; Gonzalez-Rico, Jorge; Lopez-Donaire, Maria Luisa; Arias, Angel; Garcia-Gonzalez, Daniel (Composites Part B-Engineering, 2021)
Magnetorheological elastomers (MREs), consisting of an elastomeric matrix filled with magnetic particles, are one of the most promising multifunctional composites. The main advantage of these materials is their response to external magnetic fields by mechanically deforming and/or changing their magnetorheological properties. This multi-physical nature makes them ideal candidates for timely applications in soft robotics and bioengineering. Although several works have addressed the magneto-mechanical coupling in these composites from both experimental and modelling approaches, there is still a big gap of knowledge preventing the full understanding of their underlying physics. In this regard, there is no experimental work addressing a comprehensive magneto-mechanical characterisation combining different MRE configurations, mechanical deformation modes and magnetic conditions. Furthermore, the interplays of rate dependences into such magnetorheological behaviour still remain elusive. In this work, we provide an unprecedented experimental characterisation of a soft MRE considering more than 100 different experimental conditions involving more than 600 tests. The experiments include monotonous uniaxial compression at different deformation rates and magnetic conditions, magneto-mechanical DMA tests, relaxation tests, oscillatory shear tests at different deformation rates and magnetic conditions, magneto-mechanical shear frequency sweep tests, and novel magneto-mechanical experiments. The results obtained in this work provide full characterisation of soft MREs with a special focus on rate dependences, forming the basis to explain novel multifunctional mechanisms identified behind their coupled response. In addition, it opens the door to new constitutive and modelling approaches.
Created from Fastlane, Scopus look-up
Keywords: Experimental mechanics; Magneto-mechanical rheology; Magneto-rheological elastomers (MREs); Multifunctional composites; Smart materials; Viscoelasticity